2011
DOI: 10.3844/ajassp.2011.413.419
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Effects of Melatonin on Sodium Valproate-Induced Neural Tube Defects and Skeletal Malformations in Rat Embryos

Abstract: Problem statement: Some reports showed the teratogenic effects of sodium valproate can be prevented by application of antioxidant drugs and stimulation of the maternal immune system. Therefore, in this study, the prophylactic effect of melatonin on teratogenic effects of sodium valproate was compared. Approach: This study was performed on 31 pregnant rats that were divided into five groups. Control group received normal saline and test groups received sodium valproate (300 mg kg ), intraperitonealy at 8-9th da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…For example, Sprague Dawley rats administered VPA at 400 mg/kg/d via oral gavage from gestational day 7-18 exhibited cardiovascular, vertebral, and rib defects, as well as hypoplastic bladder, ectrodactyly, and hydronephrosis, whereas higher doses resulted in embryo resorption and lower doses resulted in less severe malformations. 11 Approximately 20% of the offspring of Wistar rats administered VPA at 300 mg/ kg intraperitoneally (ip) on the 8-9th day of pregnancy were found to have birth defects, such as spina bifida, cleft palate, and exencephaly, 12 whereas receiving 600 mg/kg VPA subcutaneously (sc) twice on gestational day 9 resulted in spina bifida occulta in 100% of exposed fetuses. 13 Mouse studies have found strain-dependent effects, with some strains exhibiting higher rates of rib fusion following 200 mg/kg ip VPA than others, 14 suggesting an underlying genetic susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sprague Dawley rats administered VPA at 400 mg/kg/d via oral gavage from gestational day 7-18 exhibited cardiovascular, vertebral, and rib defects, as well as hypoplastic bladder, ectrodactyly, and hydronephrosis, whereas higher doses resulted in embryo resorption and lower doses resulted in less severe malformations. 11 Approximately 20% of the offspring of Wistar rats administered VPA at 300 mg/ kg intraperitoneally (ip) on the 8-9th day of pregnancy were found to have birth defects, such as spina bifida, cleft palate, and exencephaly, 12 whereas receiving 600 mg/kg VPA subcutaneously (sc) twice on gestational day 9 resulted in spina bifida occulta in 100% of exposed fetuses. 13 Mouse studies have found strain-dependent effects, with some strains exhibiting higher rates of rib fusion following 200 mg/kg ip VPA than others, 14 suggesting an underlying genetic susceptibility.…”
Section: Introductionmentioning
confidence: 99%